Peningkatan Kemampuan Perempuan dalam Mewujudkan Diversifikasi Pangan Rumah Tangga di Desa Teratak Kecamatan Batukliang Utara, Kabupaten Lombok Tengah - Hayati Hayati; Arifuddin Sahidu; Muktasam Muktasam; Johan Bachri (Jurnal Gema Ngabdi, 2020)
Women in Teratak Village, North Batukliang District, Central Lombok Regency are still seen as the main actors in the realization of household food security. Teratak Village, especially Benjor Village, has potential yard and water resources that have not been used optimally as a source of household food and human resources that are united. Therefore, increasing women's abilities are needed.This activity was carried out through a series of extension activities by utilizing the potential of resources are carried out using participatory methods, namely brainstorming, lectures, discussions, games, demonstrations/practices, and competitions to prepare a variety and nutritious food. The implementation of the activities was directly carried out by the team which also acts as a guest speaker, and was also involved private extension workers and civil servant of extension workers in the framework of creating networks and program sustainability. The implementation of extension activities were smoothly and effectively; the women were very enthusiastic to participating in each activity. The results shows that the extention were considered positive and felt very beneficial for women. Women already have groups as a forum for learning and collaboration; and also have increased knowledge, positive attitudes and abilities in realizing the diversification of household food which is characterized by the ability to cultivate vegetables and raising freshwater fish, compile diet and provide diverse and nutritious food